Gender Discrimination in the Hiring of Skilled Professionals in Two Male-Dominated Occupational Fields: A~Factorial Survey Experiment with Real-World Vacancies and Recruiters in Four European Countries - Ariane Bertogg; Christian Imdorf; Christer Hyggen; Dimitris Parsanoglou; Rumiana Stoilova (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
The present article investigates gender discrimination in recruitment for two male-dominated occupations (mechanics and IT professionals). We empirically test two different explanatory approaches to gender discrimination in hiring; namely, statistical discrimination and taste-based discrimination. Previous studies suggest that, besides job applicants' characteristics, organisational features play a~role in hiring decisions. Our article contributes to the literature on gender discrimination in the labour market by investigating its opportunity structures located at the recruiter, job and company level, and how gender discrimination varies across occupations and countries.The analysed data come from a~factorial survey experiment conducted in four countries (Bulgaria, Greece, Norway and Switzerland). Real job advertisements were sampled, and the recruiters in charge of hiring for these positions (n =0.167em1,920) rated up to ten hypothetical CVs (vignettes). We find gender discrimination in Bulgaria and Greece and to a~lesser degree in Switzerland, but not in Norway. The degree of gender discrimination appears to be greater in mechanics than in IT. Multivariate analyses that test a~number of opportunity structures for discrimination suggest that mechanisms of statistical discrimination rather than those of taste-based discrimination might be at work.
Keywords: 300; Gender Gap; Recruiting; Vacancies; STEM; Vignette Study; Comparative study; Gender Gap; Rekrutierung; Stellenausschreibungen; MINT; Faktorieller Survey; Internationaler Vergleich